Incentive compatibility in multi-unit auctions - BIKHCHANDANI, Sushil (Institutional Knowledge at Singapore Management University, 2003)
We characterize incentive compatibility in multi-unit auctions with multi-dimensional types. An allocation mechanism is incentive compatible if and only if it is nondecreasing in marginal utilities (NDMU). The notion of incentive compatibility we adopt is dominant strategy in private value models and ex post incentive compatibility in models with interdependent values. NDMU is the following requirement: if changing one buyer’s type, while keeping everyone else’s types the same, changes this buyer’s allocation then the new allocation must be relatively more attractive (or relatively less unattractive) to this buyer. We also establish a price characterization of incentive compatible mechanisms.